2021
DOI: 10.1155/2021/5553820
|View full text |Cite
|
Sign up to set email alerts
|

Study on Finite Element Model of the Prefabricated Reinforced Concrete Beam‐Column Joints with Grouted Sleeves

Abstract: Based on the monotonic tensile test of grouted sleeve specimens conducted, this paper uses multifactor regression analysis to construct the equivalent constitutive relationship of grouted sleeve specimens under uniaxial tension. The study based on this constitutive relationship of grouted sleeves and the effect of bond and slip between steel and concrete were considered. The prefabricated reinforced concreted beam-column joints with grouted sleeves were presented with finite element software ABAQUS. The seismi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…An accurate constitutive model of grouted sleeve splice will increase the efficiency of structural design [26]. In terms of efficient finite element calculation, the solid element of a grouted sleeve splice can be replaced by a truss element utilizing a constitutive model [27]. Haber and Saiidi [28] confirmed that a constitutive model can be used to simplify the finite model of columns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An accurate constitutive model of grouted sleeve splice will increase the efficiency of structural design [26]. In terms of efficient finite element calculation, the solid element of a grouted sleeve splice can be replaced by a truss element utilizing a constitutive model [27]. Haber and Saiidi [28] confirmed that a constitutive model can be used to simplify the finite model of columns.…”
Section: Introductionmentioning
confidence: 99%
“…A statistical method using SPSS software was proposed to fit the load-deformation model of grouted sleeve splice. Luo [23] used this method to fit 26 groups of specimens and obtain the constitutive model of grouted sleeve splice. Then they verified this model with a finite element analysis of beam-column joints, and their results showed a good agreement with the test results.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the rack is an important component, especially the mechanical characteristics of the rack play an important role in the working performance of the entire equipment. At present, the structural design and optimization of mechanical equipment have moved from previous experience, analogy, and static design to modeling, optimization, and dynamic design [3][4][5][6][7]. Therefore, the Pro/E, ANSYS and other modern engineering software platforms have been applied in this article to conduct mechanical analysis of rack on the JC-17B mobile lifting jack, and the optimization design of rack on the JC-17B mobile lifting jack has been completed, for the future of all types of mobile lifting jack development, technological transformation and equipment renewal provides a reliable basis for the design.…”
Section: Introductionmentioning
confidence: 99%